Peran Locus Of Control Internal Terhadap Kemampuan Pemecahan Masalah Akademik Pada Mahasiswa Pengurus Organisasi - Neni Widyayanti; Hazanariah Hazanariah; Nadea Zulfa Khairunnisa (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
This study aims to examine the relationship between internal locus of control and academic problem solving skill in student organization. The hypothesis in this study is that there is a positive relationship between internal locus of control and the ability to solve academic problems in organizational students. Research respondents (N = 200) are active students, are administrators or active members in community service and are aged 17-22 years. Collecting data using academic problem solving skill scale and internal locus of control scale. The analysis in this study was tested with a correlation technique, namely Spearman carried out using the help of SPSS for Windows version 22.00. The results of the analysis show that there is a significant positive relationship between internal locus of control and academic problem solving abilities in student organizations.